Transgranichnaja korporativnaja integracija v Baltijskom regione [Transborder corporate integration in the Baltic Sea Region] - Kuznetsov A. V. (Балтийский регион, 2012)
The paper examines flows of foreign direct investment within the Baltic region. The author demonstrates close investment ties among the EU members, which are of special importance for Estonia, Latvia and Lithuania. Transborder corporate integration in the region is characterized by significant imbalances. In many aspects, it can be viewed as Sweden’s economic expansion or development of domestic markets for northern European companies. Although many German, Polish and Russian companies are involved in corporate integration in the Baltic region, other vectors of their foreign economic relations are still more important for them. As a result, the integration of Russian business in the Baltic part of the European integration area is still rather weak despite Russia’s considerable foreign direct investment in the Baltic States.